Catholic Clergy of Italian Nationality in the British Middle East, 1939–1944 - Pili, Jacopo (The journal of ecclesiastical history, 2024)
During the Second World War, the British Government interned or asked the Holy See to replace many of the Italian clergy within the territories that it controlled. This led to a political conflict between London and the Vatican which was not resolved until the end of the war. This article addresses the development of the controversy and its causes, concluding that it stemmed from traditional imperial hegemonic goals rather than from anti-Catholicism. It also stresses that the Church's response was weakened by national rivalries within the Catholic clergy in the region, and the fundamentally different views of the war of London and the Vatican.